2013
DOI: 10.1177/0003319713489769
|View full text |Cite
|
Sign up to set email alerts
|

Monitored Daily Ambulatory Activity, Inflammation, and Oxidative Stress in Patients With Claudication

Abstract: We determined the association between daily ambulatory activity and markers of inflammation and oxidative stress in patients with peripheral artery disease (PAD) and claudication. Patients with PAD (n=134) limited by claudication were studied. Patients took 3275±1743 daily strides during 273±112 min each day, and their average daily cadence was 11.7±2.7 strides/min. High-sensitivity C-reactive protein was significantly and negatively associated with the total number of daily strides (p<0.001), total daily ambu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 36 publications
3
34
0
Order By: Relevance
“…38 The time to reach minimum calf muscle StO 2 is a key measure of microcirculatory function during exercise, as this measure is positively associated with COT and PWT, and negatively associated with ischemic window in patients with intermittent claudication. 28 High daily ambulatory activity is associated with less impaired calf muscle StO 2 during exercise in women with PAD, 17 and with lower inflammation in PAD, 39 suggesting that an exercise intervention may improve microcirculatory function and inflammation. Furthermore, pharmacologic therapy to improve inflammation and microcirculation of women with PAD should be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…38 The time to reach minimum calf muscle StO 2 is a key measure of microcirculatory function during exercise, as this measure is positively associated with COT and PWT, and negatively associated with ischemic window in patients with intermittent claudication. 28 High daily ambulatory activity is associated with less impaired calf muscle StO 2 during exercise in women with PAD, 17 and with lower inflammation in PAD, 39 suggesting that an exercise intervention may improve microcirculatory function and inflammation. Furthermore, pharmacologic therapy to improve inflammation and microcirculation of women with PAD should be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…7, 10, 11 We have reported that circulating inflammatory biomarkers are associated with community-based daily walking in symptomatic patients with PAD, but it is not known whether physical activity modifies circulating antioxidant capacity. 12 It is established that physical activity reduces oxidative stress and increases the ability to respond to oxidative challenges in older adults, suggesting that antioxidant capacity may be increased in older adults who are physically active. 1316 However, the influence of monitored daily walking on antioxidant capacity in symptomatic patients with PAD, who typically have greater cardiovascular burden and inflammation than healthy older adults, has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…1316 However, the influence of monitored daily walking on antioxidant capacity in symptomatic patients with PAD, who typically have greater cardiovascular burden and inflammation than healthy older adults, has not been addressed. 12, 1719 …”
Section: Introductionmentioning
confidence: 99%
“…Physical inactivity is one factor that may negatively impact vascular biomarkers in patients with PAD 5 . More recently, sedentary behavior has emerged as an important cardio-metabolic risk factor in the general population 6-8 , as greater time spent in sedentary activities is associated with type 2 diabetes, fatal and nonfatal cardiovascular disease, and all-cause mortality 6-8 .…”
Section: Introductionmentioning
confidence: 99%